Optimasi Gripper Dua Lengan dengan Menggunakan Metode Genetic Algorithm pada Simulator Arm Robot 5 DOF (Degree of Freedom) - Andy Rahmawan; Munadi Munadi; Toni Prahasto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2013)
An arm robot simulator 5dof (degree of freedom) which is equipped with a two-finger gripper is designed to determine the movement of the robot manipulator. To make an arm robot simulator, we used acrylic as a base material, servomotor as a driver and an Arduino Uno SMD as microcontroller. Acrylic was chosen because it is light, strong and durable. Arduino Uno SMD was chosen because it can interact with LabVIEW that will be able to control the movement angle of servomotor manually. The purpose of this final project is to make an arm robot simulator 5 dof which equipped a gripper and optimization of two finger gripper configuration use one of optimization techniques, the genetic algorithm optimization. For making the link of simulator, we use the acrylic laser cutting machine to be more precision cutting. Servomotor’s movement is controlled by using a program that was created using LabVIEW. Servomotor’s angle position error was corrected by using program functions of numerical multiply and numerical divided on LabVIEW. Optimization of gripper configuration using MATLAB software as a tool for the calculation. A genetic algorithm optimization used the default parameters, then the calculation result are always different. All the results of these calculations are correct and it affects the shape of the gripper configuration at zmax. Then the torque of gripper before optimized and after optimized can be obtained.